Higher Fungi of Northeast Langkawi - Abdullah, Noorlidah; S, Vikineswary,; M, Yusoff,; Dennis E, Desjardin, (Malaysian Journal of Science, 2005)
The North-East Langkawi is unique with different ecosystems and diverse forest types which are relatively undisturbed. A total of 212 specimens were collected from eight localities in the North-East Langkawi during two sampling periods from 10 - 19 April 2003 and 4 - 9 April 2004. The highest number of macrofungi collected was from Gunung Raya and Sungai Sireh Forest Reserves which are richly forested with predominantly dipterocarp trees. Twenty-two specimens were identified to species and 153 specimens were identified to genus. Macrofungi from the Division Ascomycota and Subdivision Ascomycotina recorded were Xylaria spp. (4 specimens) from Xylariaceae and Phillipsia sp. (1 specimen) from Sarcoscyphaceae. Further, 71 genera of Basidiomycotina belonging to 8 orders and 25 families were among the identified specimens. The Agaricales was the dominant order documented with 42 genera from eleven families recorded. The frequently recorded genera were Marasmius (29 specimens) followed by Lentinus (13 specimens) and Gymnopus and Polyporus (9 specimens each). The Marasmius specimens belonged to Marasmius sect. Marasmius (15 specimens), Marasmius sect. Sicci (6 specimens), Marasmius sect. Globulares (1 specimen) and seven unknown.